Association between Gustave Roussy Immune Score and delay in discharge among children and adolescents with mycoplasma pneumoniae pneumonia: a retrospective cohort study - Zhou, Xu; Zhang, Baoqing; Li, Yanning; Zhao, Xingyou (Frontiers in Pediatrics, 2025)
BackgroundMycoplasma pneumoniae pneumonia (MPP) is one of the leading causes of hospitalization and death in children. Epidemiological studies have confirmed that single blood indicators such as the neutrophil-to-lymphocyte ratio (NLR), lactic dehydrogenase (LDH), and albumin (Alb) levels are associated with the prognosis and length of stay (LOS) of patients with MPP. In this study, we aim to evaluate the association of the GRIm score with the LOS and compare its strength of association with that of its individual components.MethodsWe recruited 786 children with MPP who were admitted to the Affiliated Hospital of Shandong University of Traditional Chinese Medicine during the period between 2014 and 2021. The end of follow-up was discharge. Univariate and multivariate logistics regression models were used to explore the association between the NLR, LDH, Alb as well as the GRIm score with the LOS among our cohort, with odd ratios (ORs) and 95% confidence intervals (CIs). The receiver operating characteristic (ROC) curve, the net reclassification improvement (NRI) index, and the integrated discrimination improvement (IDI) index were used to compare the predictive efficacy of the GRIm score with the NLR and LDH and in predicting the LOS among children and adolescents with MPP.ResultsAfter the application of the inclusion and exclusion criteria, 389 eligible children and adolescents with MPP were included, with a mean age of 5.21 (±2.59 years). After adjusting for covariates, we found that LDH and the GRIm score were positivity associated with the LOS (LDH: β = 0.40, 95% CI: 0.00–0.80; GRIm score: β = 0.33, 95% CI: 0.07–0.58). The high GRIm score was associated with an LOS ≥7 or 11 days (≥7 days: OR = 0.635, 95% CI: 0.585–0.685; ≥ 11 days: OR = 0.622, 95% CI: 0.543–0.700). The area under the curve (AUC), NRI, and IDI all showed that the GRIm score had excellent ability in predicting the LOS of children with MPP compared with single indicators such as LDH, the NLR, and Alb.ConclusionThe GRIm score showed a significant association with the prolonged LOS in children with MPP, and the strength of this association was higher than its individual components. However, these findings still need to be confirmed by further large multicenter prospective cohort studies.